Regulation of Aldo–Keto Reductases in Human Diseases - Chen, Wei-Dong; Zhang, Yanqiao (Frontiers in Pharmacology, 2012)
The aldo-keto reductases (AKRs) are a superfamily of NAD(P)H-linked oxidoreductases, which reduce aldehydes and ketones to their respective primary and secondary alcohols. AKR enzymes are increasingly being recognized to play an important role in the transformation and detoxification of aldehydes and ketones generated endogenously and exogenously during drug detoxification and xenobiotic metabolism. Many transcription factors have been identified to regulate the expression of human AKR genes, which could have profound effects on the metabolism of endogenous mediators and detoxication of chemical carcinogens. This review summarizes the current knowledge of AKR regulation by transcription factors and other mediators in human diseases.